Adaptasi Dakwah Virtual Lembaga Dakwah Islam Indonesia (LDII) Semarang Barat Pasca Pandemi Covid 19 (New Normal Era) - Reni Megawati; Muhammad Lukman Ihsanuddin (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2021)
Dakwah is the delivery of messages in the form of an invitation to the community towards the path of truth. The existence of covid 19 as a pandemic that spreads almost all over the world, is a problem for all Muslims. There is a transition period from direct da'wah to da'wah through social media. Preparation of adequate equipment and knowledge is very much needed for the continuity of da'wah by LDII West Semarang. So a da'wah strategy is needed to keep it running during this pandemic. This study explores the da'wah strategy of the Indonesian Islamic Da'wah Institute (LDII) West Semarang in the new normal era through virtual communication media. The method used in this research is descriptive qualitative. Collecting data through interviews and collecting secondary data sources from the West Semarang LDII online portal. The findings of this study provide an overview of LDII West Semarang's da'wah activities that have adapted to new da'wah activities through virtual communication media to become more diverse and widespread. The Indonesian Islamic Da'wah Institute is able to consistently communicate da'wah messages to mad'u through virtual media such as Zoom (video conference) and Senkom Digital Communication (recording conference).Keyword: Strategy, Da’wah, LDII, New Normal EraABSTRAKDakwah merupakan penyampaian pesan berupa ajakan kepada masyarakat menuju jalan kebenaran. Adanya covid 19 sebagai pandemi yang tersebar hampir seluruh dunia, menjadi persoalan bagi seluruh kaum muslim. Terdapat masa transisi dari dakwah secara langsung menjadi dakwah melalui media sosial. Penyiapan perangkat dan pengetahuan yang memadai sangat dbutuhkan untuk keberlangsungan dakwah oleh LDII Semarang Barat. Maka diperlukan strategi dakwah agar tetap berjalan di masa pandemi ini. Penelitian ini menggali strategi dakwah Lembaga Dakwah Islam Indonesia (LDII) Semarang barat di era new normal melalui media komunikasi virtual. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Penggalian data melalui wawancara dan mengumpulkan sumber data sekunder dari portal online LDII Semarang Barat. Temuan dari penelitian ini memberikan gambaran kegiatan dakwah LDII Semarang Barat yang beradaptasi dengan aktivitas dakwah baru melalui media komunikasi virtual menjadi lebih beragam dan meluas. Lembaga Dakwah Islam Indonesia mampu mengkomunikasikan pesan – pesan dakwah secara konsisten kepada mad‟u melalui media virtual seperti Zoom (video conference) dan Senkom Digital Communication (recording conference).Kata Kunci: Strategi, Dakwah, LDII, era new normal